Macrocellular Titanosilicate Monoliths as Highly Efficient Structured Olefin Epoxidation Catalysts - Smeets, Valentin; van den Biggelaar, Ludivine; Barakat, Tarek; Gaigneaux, Eric M.; Debecker, Damien P. (ChemCatChem, 2019)
Self‐standing macrocellular titanosilicate monolith foams are obtained using a one‐pot sol‐gel route and show excellent performance in the epoxidation of cyclohexene. Thanks to the High Internal Phase Emulsion (HIPE) templating method, the materials feature a high void fraction, a hierarchically porous texture and good mechanical strength. Highly dispersed Ti species can be incorporated in tetrahedral coordination in the silica matrix. These characteristics allow the obtained ‘SiTi(HIPE)’ materials to reach high catalytic turnover in the epoxidation of cyclohexene. The monoliths can advantageously be used to run the reaction in continuous flow mode. Hype the HIPE: Self‐standing titanosilicate monolith foams obtained using the High Internal Phase Emulsion (HIPE) templating method, present hierarchical porosity, high Ti dispersion, and reach high TOF in the epoxidation of cyclohexene. A flow‐mode olefin epoxidation process is demonstrated.